2016
DOI: 10.1096/fj.201600784r
|View full text |Cite
|
Sign up to set email alerts
|

Development of original metabolically stable apelin‐17 analogs with diuretic and cardiovascular effects

Abstract: Apelin, a (neuro)vasoactive peptide, plays a prominent role in controlling cardiovascular functions and water balance. Because the in vivo apelin half-life is in the minute range, we aimed to identify metabolically stable apelin-17 (K17F) analogs. We generated P92 by classic chemical substitutions and LIT01-196 by original addition of a fluorocarbon chain to the N terminus of K17F. Both analogs were much more stable in plasma (half-life >24 h for LIT01-196) than K17F (4.6 min). Analogs displayed a subnanomolar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
63
0
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 50 publications
(73 citation statements)
references
References 47 publications
1
63
0
9
Order By: Relevance
“…However, K17F is 30 times more potent in inducing rat ApelinR internalization when compared to pE13F (33). Deletion of the C-terminal Phe of K17F (K16P) or its substitution by an alanine (K17A) strongly decreases the ability of the peptide to trigger ApelinR internalization without effect on its affinity for the ApelinR or its ability to activate Gαi-coupling (18, 20).…”
Section: Metabolism Of Apelin Peptides and Pharmacological Characterimentioning
confidence: 99%
See 4 more Smart Citations
“…However, K17F is 30 times more potent in inducing rat ApelinR internalization when compared to pE13F (33). Deletion of the C-terminal Phe of K17F (K16P) or its substitution by an alanine (K17A) strongly decreases the ability of the peptide to trigger ApelinR internalization without effect on its affinity for the ApelinR or its ability to activate Gαi-coupling (18, 20).…”
Section: Metabolism Of Apelin Peptides and Pharmacological Characterimentioning
confidence: 99%
“…In addition, Gerbier et al (33) showed that K17F and pE13F have a half-life in mouse plasma of 4.6 and 7.2 min, respectively, and Murza et al (42) showed that pE13F has a 14 min half-life in rat plasma. Regarding apelin-36, Japp et al (43) suggested from experiments conducted in healthy human subjects that the half-life of apelin 36 is lower than 5 min.…”
Section: Development Of Metabolically Stable Apelin Analogsmentioning
confidence: 99%
See 3 more Smart Citations